Individualization of the three‐piece base arch mechanics according to various periodontal support levels: A finite element analysis. (1st September 2020) - Gameiro, Gustavo Hauber; Bocchiardo, Jorge Eugenio; Dalstra, Michel; Cattaneo, Paolo Maria
Abstract: Introduction: The orthodontic correction of periodontally compromised dentitions constitutes a huge challenge in the clinical practice of adult orthodontics. The biological and physical distinct features of these conditions require a carefully designed mechanical plan for the successful treatment of these complex cases. Setting and Sample Population: A segment of a human maxilla containing the central and lateral incisors, obtained from autopsy, was scanned with microcomputed tomography, and a finite element (FE) model was generated to represent an intact periodontal dentition. Based on this model, three additional models simulating a mild, moderate and severe bone alveolar loss were created as well. Materials and Methods: Two loading scenarios for the application of intrusive and retraction mechanics with a three‐piece base arch appliance were evaluated in a series of FE analyses. The tooth displacements and strains in the periodontal ligament (PDL) were calculated and compared for the four FE models. Results: The periodontal reduced dentitions exhibited a similar axis of resistance for intrusive mechanics, but the axis of resistance for retraction movements was significantly dependent on the degree of alveolar bone loss. The tooth displacements and PDL loads were higher in the reduced dentitions for both intrusive and retraction mechanics. Conclusions: A reduction in the force levels applied to periodontal reduced dentitions is indicated, and a customized selection of appropriate points of force application is needed according to the specific amount of alveolar bone loss.